Comparison of Risk Factors for Pediatric Kidney Stone Formation: The Effects of Sex - Schwaderer, Andrew L.; Raina, Rupesh; Khare, Anshika; Safadi, Fayez; Moe, Sharon M.; Kusumi, Kirsten (Frontiers in Pediatrics, 2019)
Urinary stones are affecting more children, and pediatric stone formers have unique pathophysiology compared to adults. While adult stone formers are most frequently male, children have an age dependent sex prevalence. Under 10 years, a majority of stone formers are boys; adolescent stone formers are mostly female. . Previous adult studies have shown that stone composition is influenced by the sex and age of the stone former. Thus, we hypothesize that female and male stone forming children will also have sex and age specific stone phenotypes.